Studying anthocyanins in the skin and flesh of the tubers of some potato hybrids (Solanum tuberosum L.) - I. V. Kim; A. G. Klykov (Овощи России, 2024)
Relevance. Today special attention is paid to potato anthocyanins as components of functional food. Increasing interest is generated by research on the use of anthocyanins for the benefit of animals and people in addition to their significant role in the life of plants.   The research goal was to identify the quantitative and qualitative composition of anthocyanins in the tubers of valuable potato hybrids of Primorsky selection.   Five promising potato hybrids (Solanum tuberosum L.) belonging to different groups of maturity and involved in the comparative variety testing by FSBSI “FSC of Agricultural Biotechnology named after A. K. Chaiki” were used as the research object.   The research was carried out under the conditions of field and laboratory experiments in Primorsky kray, Russia, in 2018-2023. The anthocyanins were divided by the method of high-performance liquid chromatography. The anthocyanins were identified by the method of second-order mass spectrometry.   Results. The research evaluated the potato hybrids for the content of anthocyanins in the tissues of the tubers – skin and flesh. The following specimens were determined to have a high content of anthocyanins both in the skin and flesh: Pri-15-12-14 (petunidin-3-arabinoside: 310.0 and 91.1 mg/kg; cyanidin-3-glucoside: 149.8 and 39.8 mg/kg) and Pri-14-52-2 (petunidin-3-arabinoside: 360.0 and 143.0 mg/kg; cyanidin-3-glucoside: 80.4 and 81.2 mg/kg). The selected specimens were characterized by purple and blue-purple skin. Genotypes Pri-14-52-2 and Pri-15-12-14 had tuber flesh with purple pigmentation. Hybrids Pri-15-12-14 and Pri-14-52-2 had the highest total content of anthocyanins in the flesh – 130.9 and 224.2 mg/kg, respectively. The conducted research identified eight different anthocyanins in the tubers of the studied potato specimens: delphinidin-3-glucoside, delphinidin-3-ramnosil-5-glucoside, petunidin-3-glucoside, malvidin-3-glucoside, cyanidin-3-glucoside, cyanidin-3-ramnosil-5-glucoside, pelargonidin-3-glucoside, and petunidin-3-arabinoside. The tubers with pink and red skin were determined to contain pelargonidin-3-glucoside. Petunidin-3-glucoside and cyanidin-3-glucoside colored tuber skin purple. The selected group of specimens might be recommended for use as functional food and in goal-oriented breeding.